Fillier. North River. Photograph of children posing in armchair. (1965)
A photograph of 5 children, 1 boy, 3 girls, and 1 baby, posing in an armchair with nice outfits. Left to right: Sandra (Fillier) Snow, Art Fillier, Juanita (Fillier) Mackey, Marge Fillier, Cherie (Fillier) Wilhelm.